Image_11.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
A portion of the dough is taken and flattened into a round shape by pressing it against a flat surface. The pressing is done entirely by hand, which takes considerable skill. In contrast to how rotis are made in other parts of India, a rolling pin is not used. The ideal bhakri should be of uniform size and thickness, which may take years of hands-on experience to perfect.